Molecular divergence of the W chromosomes in pyralid moths (Lepidoptera) - Vítková, Magda; Fuková, Iva; Kubícková, Svatava; Marec, Frantisek (Chromosome research, 2007)
Most Lepidoptera have a WZ/ZZ sex chromosome system. We compared structure of W chromosomes in four representatives of the family Pyralidae--Ephestia kuehniella, Cadra cautella, Plodia interpunctella, and Galleria mellonella--tracing pachytene bivalents which provide much higher resolution than metaphase chromosomes. In each species, we prepared a W-chromosome painting probe from laser-microdissected W-chromatin of female polyploid nuclei. The Ephestia W-probe was cross-hybridized to chromosomes of the other pyralids to detect common parts of their W chromosomes, while the species-specific W-probes identified the respective W chromosome. This so-called Zoo-FISH revealed a partial homology of W-chromosome regions between E. kuehniella and two other pyralids, C. cautella and P. interpunctella, but almost no homology with G. mellonella. The results were consistent with phylogenetic relationships between the species. We also performed comparative genomic hybridization, which indicated that the W chromosome of C. cautella is composed mainly of repetitive DNA common to both sexes but accumulated in the W chromosome, whereas E. kuehniella, P. interpunctella, and G. mellonella W chromosomes also possess a large amount of female specific DNA sequences, but differently organized. Our results support the hypothesis of the accelerated molecular divergence of the lepidopteran W chromosomes in the absence of meiotic recombination.
Keywords: malování chromozomů; druhová specificita; Sex Chromosomes; Male; pohlavní chromozomy; hybridizace in situ fluorescenční; můry; Chromosome Painting; Pachytene Stage; pachytenní stadium; biologická evoluce; mužské pohlaví; hybridizace nukleových kyselin; Species Specificity; Animals; ženské pohlaví; Biological Evolution; Sex Differentiation; zvířata; In Situ Hybridization, Fluorescence; sexuální diferenciace; Female; Nucleic Acid Hybridization; Moths